Treatment of dry age-related macular degeneration with dobesilate. (22nd June 2012) - Cuevas, P; Outeiriño, L A; Angulo, J; Giménez-Gallego, G
Abstract : The authors present anatomical and functional evidences of dry age-macular degeneration improvement, after intravitreal treatment with dobesilate. Main outcomes measures were normalisation of retinal structure and function, assessed by optical coherence tomography, fundus-monitored microperimetry, electrophysiology and visual acuity. The effect might be related to the normalisation of the outer retinal architecture.